2020
DOI: 10.3390/plants9060680
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Chemical Variability in Oliveria decumbens (Apiaceae) from Different Regions of Iran and Its Relationship with Environmental Factors

Abstract: Oliveria decumbens Vent. (Apiaceae) is an annual herb resistant to harsh environmental conditions, which has got numerous pharmacological, food and feed, and cosmetic applications. In the present study, the variation in the essential oil (EO) content and composition of twelve O. decumbens populations growing wild in several habitats of Iran was studied. The EO contents varied from 2.71% (Darab) to 8.52% (Behbahan) on a dry matter basis, where the latter population revealed to be the highest source of essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…γ-Terpinene, which is related to the biosynthesis of the phenolic monoterpenes [42], showed an inverse trend, with the highest percentage (25.9%) in the essential oil from the Kahnoyeh population, and the lowest one in that from Nourabad Mamasani (13%). A similar trend was observed for p-cymene, with the oil from Behbahan population containing the highest percentage (17.3%), and that from Nourabad Mamasani showing the lowest value (9.5%) [33].…”
Section: Essential Oil Compositionsupporting
confidence: 75%
See 4 more Smart Citations
“…γ-Terpinene, which is related to the biosynthesis of the phenolic monoterpenes [42], showed an inverse trend, with the highest percentage (25.9%) in the essential oil from the Kahnoyeh population, and the lowest one in that from Nourabad Mamasani (13%). A similar trend was observed for p-cymene, with the oil from Behbahan population containing the highest percentage (17.3%), and that from Nourabad Mamasani showing the lowest value (9.5%) [33].…”
Section: Essential Oil Compositionsupporting
confidence: 75%
“…A number of various factors, including genetics, soil, geographic, and climatic conditions affect the essential oil content [40]. In addition, some factors like altitude have been reported to affect the essential oil content [33,40,41]. In our study, the highest content was found in the essential oil from Behbahan population growing at the lowest altitude (394 m), followed by that from Kahnoyeh and Dehdasht populations located at 758 and 971 m a.s.l., respectively.…”
Section: Essential Oil Contentmentioning
confidence: 46%
See 3 more Smart Citations